2015
DOI: 10.1021/acs.analchem.5b03158
|View full text |Cite
|
Sign up to set email alerts
|

Single-Particle Time-of-Flight Mass Spectrometry Utilizing a Femtosecond Desorption and Ionization Laser

Abstract: Single-particle time-of-flight mass spectrometry has now been used since the 1990s to determine particle-to-particle variability and internal mixing state. Instruments commonly use 193 nm excimer or 266 nm frequency-quadrupled Nd:YAG lasers to ablate and ionize particles in a single step. We describe the use of a femtosecond laser system (800 nm wavelength, 100 fs pulse duration) in combination with an existing single-particle time-of-flight mass spectrometer. The goal of this project was to determine the suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…The ns-laser spectrum is representative of 500 particles. The positive spectrum consists of NH The ns-LAAPTOF bipolar spectrum is comparable to the ammonium nitrate single-particle spectrum obtained by the PALMS (Zawadowicz et al, 2015). NH 4 NO 3 predominantly leads to positive ions (NH (Neubauer et al, 1998), but in contradiction to observations with the PALMS (Zawadowicz et al, 2015) or the real-time single-particle mass spectrometer (RSMS) with excimer laser wavelength 193 nm (Reinard and Johnston, 2008).…”
Section: Nh 4 No 3 Particlesmentioning
confidence: 65%
See 2 more Smart Citations
“…The ns-laser spectrum is representative of 500 particles. The positive spectrum consists of NH The ns-LAAPTOF bipolar spectrum is comparable to the ammonium nitrate single-particle spectrum obtained by the PALMS (Zawadowicz et al, 2015). NH 4 NO 3 predominantly leads to positive ions (NH (Neubauer et al, 1998), but in contradiction to observations with the PALMS (Zawadowicz et al, 2015) or the real-time single-particle mass spectrometer (RSMS) with excimer laser wavelength 193 nm (Reinard and Johnston, 2008).…”
Section: Nh 4 No 3 Particlesmentioning
confidence: 65%
“…We compare mass spectra of atmospherically relevant airborne particles and dedicated test particles from nsand fs-laser ablation using a commercially available laser ablation aerosol time-of-flight mass spectrometer (LAAPTOF, AeroMegt GmbH). The results presented here are an extension of the work by Zawadowicz et al (2015), who coupled a particle analysis by laser mass spectrometry (PALMS) with an fs laser (Spectra Physics Solstice-100F ultrafast laser) to investigate mass spectral patterns of NaCl, NH 4 NO 3 , and lead-doped NH 4 NO 3 particles. Overall, they observed similar mass spectra in both ns-and fs-laser ablation but also showed that ions with high ionization energy such as Cl + are more easily generated by the fs laser due to its higher power density.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The ns-LAAPTOF bipolar spectrum is comparable to the ammonium nitrate single particle spectrum obtained by the PALMS (Zawadowicz et al, 2015). NH4NO3 predominantly leads to positive ions (NH2 cluster ions are very high (Dunlap and Doyle, 1996), which may be the reason for the absence of these ions in the ns-spectra.…”
mentioning
confidence: 52%
“…The results presented here are an extension of the work by Zawadowicz et al (2015), who coupled a Particle Analysis by Laser Mass Spectrometry (PALMS) with an fslaser (Spectra Physics Solstice-100F ultrafast laser) to investigate mass spectral patterns of NaCl, NH4NO3, and lead doped NH4NO3 particles. Overall, they observed similar mass spectra in both ns-and fs-laser ablation, but 95 also showed that atoms with high ionization energy such as Cl are more easily ionized by the fs-laser due to its higher power density.…”
mentioning
confidence: 99%